The cytologic demonstration of certain enzymes in subcommissural organ of goat* - KUMAR, PAWAN; KUMAR, SURAJ; SINGH, YASHWANT (The Indian Journal of Animal Sciences, 2013)
Histologically different enzymes were studied in subcommissural organ of 10 young male goats of local mixed breed. Acid phosphatase as diffused homogeneous actiVity was locahzed throughout the ependyma and blood caplllanes whereas. alkaline phosphatase, glucose-6-phosphatase. succinic dehydrogenase and cytochrome oxidase were mainly distributed at the base of ependyma. Weak and moderate reactions were observed towards the free surface and hypendyma respectively. Cholinergic nerve fibres were demonstrated mainly at the junction of hypendyma with posterior commissure.